Analysis of resilient design by thermoacoustic adaptation of tropical urban model. Issue 4 (2nd October 2017) - Samodra, FX Teddy Badai
Abstract: Climate and urban environment changes lead to tropical building adaptation and resilient strategy. They focus especially on thermal comfort and noise propagation variation as the result of global warming and urban growth. This study analyzes a conceptual design of tropical urban model on integrated design of thermal and acoustic ( thermoacoustic) issues. By experimental measurement and simulation method using Computational Fluid Dynamics, the findings are directed to meet the standards and to recommend the new guidelines for sustainable urban building. The research location is in Surabaya as the urban tropical lowland area and Eco-House of ITS, a tropical building model in an urban environment, was built as experiment model. The results highlighted that the noise barrier should consider 5.24% of the maximum window to wall ratio (WWR) in tree dimensionally analysis, horizontally and vertically. Providing vertical ventilation is the best solution for urban density, but the orientation and its flanking noise affect the passive cooling. In general, there are some factors having a high contribution in addition to WWR, such as wind acceleration, the distance, and building material.